Analisis Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Peluang Ditinjau dari Minat Belajar Siswa - Putri, Amaliya; Afifah, Natasya Gita; Sriyanti, A.; Suharti; Munirah (Faculty of Tarbiyah and Teacher Training, 2024)
Students' mathematical problem solving abilities are an important competency that students must master. One factor that influences mathematical problem solving abilities is students' interest in learning. This research was conducted to analyze mathematical problem solving abilities in terms of interest in learning mathematics in mathematics learning. This research uses a descriptive method with a qualitative approach. The subjects of this research were all 28 students in class IX.1 of SMPN 1 Sengkang. The data collection techniques in this research were questionnaires about interest in learning, problem solving ability test questions and interviews. From the research results, it was found that students with a high interest in learning category had good problem solving abilities because they were able to fulfill three indicators of mathematical problem solving abilities, namely understanding the problem, planning a solution and implementing the solution plan. Students in the moderate learning interest category can complete problem solving questions by fulfilling two indicators of problem solving ability, namely understanding the problem and students being able to carry out a solution plan. Students in the low learning interest category can complete problem solving questions by only fulfilling one indicator of problem solving ability, namely carrying out plans.